WORKSHOP PENDAMPINGAN SURVEY KEPUASAN MASYARAKAT BAGI SURVEYOR & ASISTEN PENELITI - Agus Tri Basuki; Henri Krismawan (Adiba Aisha Amira, 2023)
The aim of community service is to help improve the ability of surveyors and research assistants in creating indicators and calculating consumer satisfaction scores. The Service Method uses data obtained through field surveys. Field survey activities consist of distributing questionnaires and recording interviews in the field. Data collection tools include observation sheets, documentary evidence, interviews, and documentation sheets. The PkM carried out uses the following stages: 1) preparation: implementation permit; and determining the location, 2) implementation of activities: carrying out workshops, assistance in calculating the results of the community satisfaction index, and assistance in creating and compiling the community satisfaction index; 3) Final Activity: Publication in the Journal is an output of service in the form of article publication. The results that will be achieved from this service are the implementation of workshops to assist in calculating the community satisfaction index (traders and consumers) at the Beringharjo market and Prawirotaman market, Yogyakarta City in accordance with the steps set and the establishment of collaboration with CV Adicaraka Semesta.